IMPLEMENTATION OF FRONT END ANALYSIS IN DEVELOPING MEANINGFUL INSTRUCTIONAL OBJECTIVES IN COASTAL SCHOOLS: A CASE STUDY - Wa Ode, Sinta Kalsum; Djono (Universitas PGRI Palembang, 2025)
One of the main drivers of human resource development is education. Particularly in coastal regions like Mantigola village, which is home to the Bajo tribe, Indonesia struggles to provide fair and high-quality education. One of the factors contributing to unequal access to education, according to the National Development Planning Agency (2014), is remote rural geographic settings. Aside from topographical issues, the primary concerns at Mantigola State Satap Middle School are inadequate infrastructure, low reading and writing literacy, and the pupils' fishing culture. The Merdeka Curriculum places a strong emphasis on creating learning experiences that are student-centered. Before establishing learning objectives, the Dick and Carey methodology provides a way to assess instructional needs using Front End Analysis (FEA). This study investigates how FEA is used at Satap Negeri Mantigola Middle School to create learning goals that are pertinent to the Merdeka Curriculum and appropriate for the students' setting. The implementation of FEA in this situation was examined using a qualitative descriptive case study methodology. The findings demonstrate how FEA aids in determining the needs, performance, and learning environments of students as well as in creating more purposeful and flexible learning objectives.